Examining the Nexus of Human Ecology and Functional Apparel among Home Economics Students in Tertiary Institutions in Lagos State, Nigeria - Owodiong-Idemeko, Boiso Maria; Idowu, Samson Adeshola; Adetona, Sekinat Ajoke; Ogabi, Temitope Felicia (NIU Journal of Educational Research, 2025)
This study examines the nexus between human ecology and functional apparel among Home Economics students in tertiary institutions in Lagos State, Nigeria. Human ecology emphasizes the dynamic relationship between individuals and their environments, while apparel serves as both a functional and expressive medium reflecting personal, cultural, and environmental values. The study adopted a descriptive survey design with a population of 300 respondents drawn from Lagos State University of Education, University of Lagos, and College of Education (Technical), Akoka. A structured online questionnaire was used to gather data on factors influencing apparel preference and the functionality of clothing to students’ environments. Data were analyzed using Chi-square and Friedman’s tests. Findings revealed significant factors influencing apparel choices, including values, cultural identity, peer group influence, institutional dress codes, climate, and fashion trends (χ² = 300.297, p < 0.001). Similarly, apparel functionality, comfort, environmental adaptability, eco-friendliness, and suitability for academic and social activities was found to significantly affect students’ environmental engagement and performance (χ² = 1311.781, p < 0.001). The study concludes that Home Economics students’ apparel preferences are shaped by a complex interaction of ecological, socio-cultural, and technological factors. It recommends the adoption of functional and eco-friendly clothing aligned with environmental conditions and institutional standards to promote comfort, identity, and professional development. Keywords: Human Ecology, Functional Apparel, Home Economics, Lagos State, Tertiary Institutions, Fashion Trends, Eco-friendly Clothing